Design of the electrical system on a general cargo ship with a length of 105,669 meters - Naval Architecture, Diva; Suardi, Suardi; Kyaw, Aung Ye; Raditya, Muhammad Yogi; Sitanggang, Syahrul Gunawan; Abdillah, Riza; Handayani, Windah (Indonesian Journal of Maritime Technology, 2023)
This research investigates the incorporation of LED lights and the zonal cavity method in the initial design stage of a cargo-type ship, focusing on efficient lighting for diverse ship zones. The study aims to determine optimal lighting requirements, adhering to industry standards, for zones such as double bottom, maindeck, poopdeck, boatdeck, bridgedeck, navdeck, and emergency conditions. Ships play a vital role in transporting passengers and goods across seas and rivers, necessitating effective lighting systems for safe operations, particularly during nighttime. This paper explores the integration of LED lights and the zonal cavity method in the general arrangement design of a cargo ship. The zonal cavity method is applied to ascertain lighting intensity in different ship zones based on room dimensions, including width, height, length, and area. Illumination values are determined according to established standards for each zone. The cumulative lighting electricity load for various ship zones using LED lights is calculated to identify specific power requirements.The lighting power requirements for the double bottom, maindeck, poopdeck, boatdeck, bridgedeck, navdeck, and emergency conditions are found to be 0.141 KW, 0.75 KW, 1.068 KW, 0.762 KW, 0.671 KW, 0.42 KW, and 0.296 KW, respectively. The total lighting power for all zones is calculated as 3.7776 KW, suggesting the installation of a 4 KW generator for optimal power supply.The application of the zonal cavity method in the planning and design of a cargo ship's lighting system, combined with energy-efficient LED lights, proves to be an effective approach. The results indicate that a 4 KW generator is sufficient to meet the lighting power demands for various ship zones, ensuring compliance with safety standards and technological advancements in maritime lighting.